Language Metafunctions in Pamungkas’s “To the Bone”: (A Systemic Functional Linguistics Analysis) - Nabilah Ani Soraya; Dwi Zalfa Zahirah; Naila ‘Ilmi Khofifah; Arya Gandhi Narendra; Reni Oktafia Agustin (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study examines Pamungkas’s song “To the Bone” through the lens of Systemic Functional Linguistics (SFL), focusing on the ideational, interpersonal, and textual metafunctions as proposed by M.A.K. Halliday. Using a qualitative descriptive approach, this research explores how the lyrics represent emotional depth, longing, and devotion through linguistic choices. The ideational metafunction reveals the representation of personal experiences and emotional states, as seen in the recurring mental processes that express desire and affection. The interpersonal metafunction highlights the close emotional relationship between the singer and the listener, employing personal pronouns, modality, and mood to convey sincerity, vulnerability, and affection. Meanwhile, the textual metafunction ensures cohesion and coherence through repetition, thematic structure, and parallelism, which emphasize the constancy of emotion and strengthen the lyrical unity. By uncovering these linguistic processes, this study demonstrates how “To the Bone” serves as a powerful medium of emotional expression, illustrating how language in music functions not only as art but also as a reflection of human intimacy and emotional truth.